Peran Media Sosial Sebagai Alat Publikasi Efektif untuk Membangun Hubungan Sekolah dan Masyarakat di SDN 181 Sukamiskin - Ihsani, Hanipa; Fitriyati, Nisa; Fatihaturohmah, Nurul; Ihsani, Virna Noor Adlida; Prihantini, Prihantini (Indo-MathEdu Intellectuals Journal, 2025)
This study discusses the role of social media as an effective publication tool in building relationships between schools and the community at SDN 181 Sukamiskin. In the increasingly fierce competition for education, schools are required not only to rely on the quality of education, but also to actively promote themselves. Social media, such as Instagram, Facebook, and other social media have proven to be effective in conveying information quickly and interactively to the wider community. This study uses a descriptive qualitative method, with data collected through observation of school social media activities and interviews. Data analysis is carried out qualitatively with the stages of data reduction, data presentation, and conclusion drawing. The results of the study show that the use of social media is able to increase community involvement and support the achievement of school programs. Social media also plays a role in maintaining a positive image of the school in the eyes of the public